Molecular Complexes of Monoammonium Glycyrrhizinate with Alphahederin and Hederasaponin C - A. Yakovishin, Leonid; I. Grishkovets, Vladimir; N. Korzh, Elena (Letters in Organic Chemistry, 2015)
Molecular complexes of monoammonium glycyrrhizinate (glycyram) with triterpene glycosides from ivy alpha- hederin (hederagenin 3-O-α-L-rhamnopyranosyl-(1→2)2)-O-α-L-arabinopyranoside) and hederasaponin C (hederagenin 3-O-α-L-rhamnopyranosyl-(1→2)-O-α-L-arabinopyranosyl-28-0-α-L-rhamnopyranosyl-(1→4)-0-β-D-glucopyranosyl-( 1→6)-0-β-D-glucopyranoside) have been prepared for the first time. The complexation has been investigated by FT-IR and UV spectroscopy. The glycosides form complexes in the 1:1 molar ratio. The allelopathic activity and ichthyotoxicity of the molecular complexes have been considered.
Keywords: Alpha-hederin